2010
DOI: 10.1017/s1368980010000479
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status, place of residence and dietary habits among the elderly: the Mediterranean islands study

Abstract: Objective: To investigate whether the socio-economic status (SES) of elderly eastern Mediterranean islanders is associated with their dietary habits, particularly with adherence to the traditional Mediterranean diet. Design: Cross-sectional. Setting: Adherence to the Mediterranean diet was measured by the MedDietScore (range: 0-55), whereas SES was estimated using education and financial status. Subjects: During 2005-2007, 300 men and women from Cyprus, 100 from Samothraki, 142 from Mitilini, 114 from Kefaloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 42 publications
6
41
0
5
Order By: Relevance
“…In the present analysis, higher education was inversely associated with hypertension, MAP, and PP levels in various countries. This in line with previous studies which have shown that higher socio-demographic status is related with better CVD health among the older adults [30]. Furthermore, diabetes and stroke were associated with hypertension and higher MAP and PP levels in many countries although the results were not as consistent as those for BMI.…”
Section: Discussionsupporting
confidence: 88%
“…In the present analysis, higher education was inversely associated with hypertension, MAP, and PP levels in various countries. This in line with previous studies which have shown that higher socio-demographic status is related with better CVD health among the older adults [30]. Furthermore, diabetes and stroke were associated with hypertension and higher MAP and PP levels in many countries although the results were not as consistent as those for BMI.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, it has been documented in many previous studies that different educational groups have healthier food choices (i.e. more adherent to the MD) probably due to increased nutrition knowledge and increased motivation to follow healthy lifestyles (6,13,(25)(26)(27)(28) . We confirmed the aforementioned trend, since participants in the medium educational category, mostly representative in the urban sample, were more likely to adhere to the MD compared with participants in the lower educational category.…”
Section: Discussionmentioning
confidence: 99%
“…Otra hipótesis, se relaciona con los hábitos de los adultos mayores; ya que en otros estudios se ha observado que un bajo nivel educativo se asocia con una menor adherencia a una dieta saludable, así como una menor realización de actividad física. 35,36 Las principales limitaciones del presente estudio se relacionan con su carácter transversal, lo cual no permite establecer asociaciones causa y efecto. Por otra parte, no se pueden generalizar los datos a la totalidad de la ciudad de Córdoba, ya que no se trató de una muestra representativa, sino intencional.…”
Section: Discussionunclassified